HUMAN DEVELOPMENT INDEX USING BAYESIAN META-ANALYSIS AND MATERNAL MORTALITY RATIO WITH CLASSIC META-ANALYSIS - Kraenau Espinal, Erwin (2011)
The objective of this research was to quantitatively synthesize the information from the Maternal Mortality Ratio (MMR) for the years 1990, 1995, 2000, 2005 and 2008 using the Classic Meta-analysis, and the Human Development Index (HDI) for the year 2010 using the Bayesian Meta-analysis combining the various investigations carried out in each country, the results obtained are shown for the regions of South America and Latin America (data used were published by the World Health Organization and United Nations Program for Development). The results for the HDI of South America and Latin America were 0.6971 and 0.6719, respectively. Additionally, the MMR for South America the 1990, 1995, 2000, 2005 and 2008 were 123, 101, 90.1,82.1 and 80.7, respectively, and MMR for Latin America at 117, 105,90.1 79.1 and 75.5, respectively. The heterogeneity of individual studies (by countries) is inherent in these measurements, which was detected using the Q test analytically and visually by Metaplot.